1999
DOI: 10.1096/fasebj.13.15.2179
|View full text |Cite
|
Sign up to set email alerts
|

The glutamate receptor antagonist MK801 modulates bone resorptionin vitroby a mechanism predominantly involving osteoclast differentiation

Abstract: Recent identification in bone of transporters, receptors, and components of synaptic signaling suggests a role for glutamate in the skeleton. We investigated effects of glutamate and its antagonist MK801 on osteoclasts in vitro. Glutamate applied to patch clamped osteoclasts induced significant increases in whole-cell membrane currents (P<0.01) in the presence of the coagonist glycine. Agonist-elicited currents were significantly decreased after application of MK801 (100 microM, P<0.01), but MK801 had no effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
78
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(83 citation statements)
references
References 33 publications
4
78
1
Order By: Relevance
“…Firstly, the receptor cross-talk that we describe here will be of significance in regulating the effect of glutamate signaling and may itself be developmentally regulated by selective expression of different NMDAR-2 s, as has been described in the brain (26,37,44,45). Interestingly, it appears that negative modulation of NMDA receptors by mGluRs does not occur in cultured osteoclasts, because the NMDA receptor currents evoked in these cells by L-glutamate and NMDA are similar (12,14). Activation of glutamatergic receptors in osteoblasts and osteoclasts can therefore elicit different [Ca 2ϩ ] i signals.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Firstly, the receptor cross-talk that we describe here will be of significance in regulating the effect of glutamate signaling and may itself be developmentally regulated by selective expression of different NMDAR-2 s, as has been described in the brain (26,37,44,45). Interestingly, it appears that negative modulation of NMDA receptors by mGluRs does not occur in cultured osteoclasts, because the NMDA receptor currents evoked in these cells by L-glutamate and NMDA are similar (12,14). Activation of glutamatergic receptors in osteoblasts and osteoclasts can therefore elicit different [Ca 2ϩ ] i signals.…”
Section: Discussionmentioning
confidence: 61%
“…2 Initial histochemical data show that nerve endings able to secrete L-glutamate may also occur within bone (16). Antagonists of NMDA receptors modulate the activities of both osteoblasts and osteoclasts, the bone cells responsible for deposition and resorbtion of bone matrix (10,14,18). These findings suggest that glutamate-mediated signaling occurs in bone, in a manner analogous to glutamatergic transmission between neurons, and that it contributes to regulation of bone matrix (19).…”
mentioning
confidence: 99%
“…NMDA is mitogenic for MC3T3-E1 osteoblastic cells and glutamate has been reported to promote the viability of primary human osteoblasts in vitro [10] . Blockade of NMDA receptors in rat primary osteoblasts inhibits expression of markers of bone formation in vitro [4,11] . Previously, we demonstrated that activation of NMDA receptors promoted rat primary osteoblast differentiation and that one of the possible mechanism was ERK1/2 activation [12] .…”
Section: Introductionmentioning
confidence: 99%
“…48 Moreover, using immunohistochemistry and reverse transcription polymerase chain reaction (RT-PCR) techniques, NMDAR1 and NMDAR2A subunits of NMDA receptors are both expressed in normal and OA chondrocytes. 49 Furthermore, both metabotropic and ionotropic glutamate receptors have been shown to be functional in osteoblasts 50 and osteoclasts, 51 and antagonists to these receptors can modify the phenotype of bone cells. 51,52 Intraarticular HA has also been demonstrated reduced PGE2 and cyclic AMP levels in the synovial fluid of OA patients; HA attenuates the inflammatory process and relieves pain by inhibiting articular chondrocytes PGE2 production.…”
Section: Discussionmentioning
confidence: 99%
“…49 Furthermore, both metabotropic and ionotropic glutamate receptors have been shown to be functional in osteoblasts 50 and osteoclasts, 51 and antagonists to these receptors can modify the phenotype of bone cells. 51,52 Intraarticular HA has also been demonstrated reduced PGE2 and cyclic AMP levels in the synovial fluid of OA patients; HA attenuates the inflammatory process and relieves pain by inhibiting articular chondrocytes PGE2 production. 14 Moreover, the viscosupplementation effect of HA may also be sensory afferent fibers and nociceptors in synovial and subsynovial tissues.…”
Section: Discussionmentioning
confidence: 99%